Technical perspectives of irrigation efficiency improvement in the oasis systems: cases of Southern Tunisia - Omrani N.; Ouessar M. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
Since the PDES (Water Master Plan of the South) in 1979 in Tunisia, the irrigation scheme has been subject to several works, to cope with the oasis expansion. The rehabilitation works aimed to overcome water losses within the distribution network. The most works were those undertaken within the framework of APIOS project (Project of irrigated area improvement in Southern Tunisia oases). Nevertheless, a continuous decrease in fossil underground water resources and their quality deterioration under intensive pumping threaten the weak ecological equilibrium of those regions. On the other hand, surface irrigation remains the main irrigation method widely used within parcels. Research review showed that farmers are still practicing over-irrigation, high amounts of water are applied and lost over the root zone, also through earth ditches. Risks of shallow water table rise and soil salinization become permanent. Under such conditions of water management, the sustainability of these ecosystems is definitely compromised. In this regard, the improvement of water distribution efficiency has to be followed by a complementary research work, aiming to enhance irrigation efficiency within farmer's parcels. The introduction of different improved surface irrigation methods should be implemented. Their adaptation to irrigation technical conditions that prevail within the oasis (water quality, water flows and available charge) has to be validated. This couldn't be reliable without further involvement of farmers and their commitment to modernize irrigation practices but they are still reluctant despite the government subsidies and encouragements for water-saving equipments within parcels.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)